A Farm to School Procurement Calculator for Specialty Crop Producers and School Food Service Staff - Jonathan A. Watson; Danielle Treadwell; Ray Bucklin; Anna Prizzia; Kelli Brew (EDIS)
Florida Farm to School programs are designed to connect producers with schools. But school food service staff make their purchasing decisions in terms of servings and producers pack their products by weight. General calculators and guides designed for national Farm to School programs don’t address Florida’s diverse production of fresh fruits and vegetables. This procurement calculator and guide for Florida Farm to School programs was written by Jonathan A. Watson, Danielle Treadwell, Ray Bucklin, Anna Prizzia, and Kelli Brew, and published by the UF Department of Horticultural Sciences, September 2014.